2007
DOI: 10.2143/ac.62.5.2023414
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Helicobacter pylori IgG titre and coronary atherosclerosis

Abstract: Helicobacter pylori IgG titres do not play an important role in the presentation of CAD and do not increase systemic inflammatory response. However, Helicobacter pylori IgG antibody titres may be correlated with the extent of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Some trials demonstrated that HP infection may have a role in the development of atherosclerosis and may be a risk factor for CAD but some did not [5][6][7][8][9]. In the present study, we confirmed the presence of a significant association between HP infection and angiographically confirmed CAD.…”
Section: Discussionsupporting
confidence: 85%
“…Some trials demonstrated that HP infection may have a role in the development of atherosclerosis and may be a risk factor for CAD but some did not [5][6][7][8][9]. In the present study, we confirmed the presence of a significant association between HP infection and angiographically confirmed CAD.…”
Section: Discussionsupporting
confidence: 85%
“…This study also revealed a reverse correlation between FMD changes and the serum level of IgG as a serological marker of H. pylori infection, for the first time. In a study by Ozdogru and colleagues, the relationship between IgG titer and the extent of coronary artery disease was reported among patients with angiography proven coronary artery disease (CAD) as well as those with acute coronary syndrome (ACS) (14) , while Hara and colleagues have rejected this kind of association (6) . This study showed a direct association between CIMT and IgG titer in chronic gastritis associated with H. pylori infection compared to the healthy subjects and furthermore compared to patients with negative H. pylori infection.…”
Section: Relationship Between Igg Level With Markers Of Endothelial Dmentioning
confidence: 99%
“…These results support the idea that past or chronic exposure to H. pylori infection, perhaps as a result of exacerbating inflammation, contributes to the onset of atherosclerosis. However, there are inconsistent data concerning markers of systematic inflammation in H. pylori-positive subjects [107][108][109] . This inconsistency can be attributed to differences in the studied ethnic groups, as different groups may develop inflammatory reactions via distinct mechanisms.…”
Section: H Pylori and Endothelial Dysfunctionmentioning
confidence: 99%